Smartphone App for Residential Testing of Formaldehyde (SmART-Form). (15th January 2019) - Zhang, Siyang; Shapiro, Nicholas; Gehrke, Gretchen; Castner, Jessica; Liu, Zhenlei; Guo, Beverly; Prasad, Romesh; Zhang, Jianshun; Haines, Sarah R.; Kormos, David; Frey, Paige; Qin, Rongjun; et al.
Abstract: Chemical contamination is ubiquitous in the indoor environment, but measurement options are often limited outside of research studies. This is especially true for formaldehyde, a known carcinogen and irritant. The goal of this project was to develop a novel screening tool: a smartphone-based app that can be paired with low-cost colorimetric badges for detection of indoor formaldehyde. The target users include citizen scientists, concerned citizens, public health nurses visiting homes, and researchers with relevant measurement needs. The user interface was designed using a collaborative development model. Badges were exposed to air for 72 h, and the user takes images that are analyzed in the phone. The app itself measures illumination (lightness) to determine color change, which was associated with formaldehyde concentration (R 2 = 0.8811, P < 0.0001). The detectable range was 20–120 ppb and the standard deviation of readings was 10.9 ppb. Warnings were integrated into the app to address current limitations, including sensitivity to extreme lighting conditions and elevated (>80%) relative humidity. Co-exposure to acetaldehyde or a VOC mixture did not interfere with measurement ( P = 0.93, P = 0.07, respectively). Overall, this screening tool can provide inexpensive, accessible information to users about their formaldehyde exposure, which can inform further testing and potential remediation activities. Highlights: A low-cost, easy-to-use screening tool measures chemical contaminants indoors by combining smartphone technology with a color-changing badge. The app was developed using a community-based approach. This enables simpler in-home contaminant measurement, with implications for environmental health professionals and citizen scientists.